The ethical concept of the fetus as a patient and the beginning of human life - Kurjak, Asim (Array, 2009)
»When does human life begin?« is not one question, but three. The first question is, »When does human biological life begin?,« and is a scientific question. A brief review of embryology is provided to answer this question. The second question is, »When do obligations to protect human life begin?,« and is a question of general theological and philosophical ethics. A brief review of major world religions and philosophy is provided to answer this question has no settled answer and therefore involves irresolvable controversy. The third question is, »How should physicians respond.